COMPARATIVE STANDARDIZATION OF MARKETED FORMULATIONS OF FERMENTED BIOMEDICINE – ARJUNARISTHA - Dheeraj Suhas Randive (Indonesian Journal of Pharmacy, 2016)
Ayurvedic formulations have proved to be effective in the prevention and treatment of many life-threatening diseases. Asavas and Arishtas have been used as medicine for over 3000 years as appetizer and stimulant. In the present study 6 different marketed brands (Two having different batches) of Arjunarishta were thoroughly evaluated for their organoleptic characteristics and physicochemical parameters, to establish a routine procedure for standardization of these Ayurvedic formulations. The organoleptic tests performed include colour, odour and taste whereas the physicochemical parameters evaluated were pH, Refractive index, Specific gravity, Viscosity, density, surface tension, Water-soluble extractive, Alcohol-soluble extractive Acid value, Alcohol content, by distillation and  dichromate oxidation method, Total solid content, Total phenol content, In present communication, a TLC method was developed for the evaluation of Arjunarishta  by quantitative estimation of major compound gallic acid and ellagic acid.